Institutions and technology as key components of national development projects: a comparative analysis of Brazil and Mexico (2014)
The absence of national projects that have attempted to institutionalize endogenous innovation capacities in Latin America has constituted a critical structural impediment to development. This article presents an analysis of themes relating to technology and development froma heterodox perspective. A large number of nations have abandoned important incipient efforts to promote a degree of technological autonomy as was undertaken during the period of state-led industrialization. This article emphasizes technology policy during the state-led era and its current possibilities. In order to ground this effort, we present a comparative analysis contrasting the diametric cases of Mexico and Brazil. We focus on national institutional structures, such as the prevailing ideology and the economic power structure, since these are the most decisive factors in the formulation of national policies governing national technological development.